¿Todavía tienes preguntas de matemáticas?

Pregunte a nuestros tutores expertos
Algebra
Pregunta

3. Transform the following expression into standar...

3. Transform the following expression into standard form \( f ( x ) = a x ^ { 2 } + b x + c \) 

\( g ( x ) = 5 ( x - 3 ) ^ { 2 } + 7 \) 

Determine the value of " \( c \) " 

Answer

3:

\(5 ( x - 3 ) ^ { 2 } + 7 = 5 x ^ { 2 } - 30 x + 52 \) 

\( \therefore g ( x ) = 5 x ^ { 2 } - 30 x + 52 \) 

\( \Rightarrow c = 52\) 

Solución
View full explanation on CameraMath App.